2021
DOI: 10.3390/jcm10194584
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Proinflammatory Cytokines and Complement Components in the Development of Drug-Induced Neuropathy in Patients with Multiple Myeloma

Abstract: The launch of novel chemotherapeutic agents—in particular, proteasome inhibitors and immunomodulatory drugs—dramatically changed multiple myeloma (MM) therapy, improving the response rate and prolonging progression-free survival. However, none of the anti-MM drugs are deprived of side effects. Peripheral neuropathy (PN) seems to be one of the most pressing problems. Despite extensive research in this area, the pathogenesis of drug-induced peripheral neuropathy (DiPN) has not yet been fully elucidated. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…It may re ect the body's anti-tumor effects. Our study found strong prognostic value for Complement 3 and IL-2R, but its role in myeloma remains unclear 44 .…”
Section: Discussionmentioning
confidence: 56%
“…It may re ect the body's anti-tumor effects. Our study found strong prognostic value for Complement 3 and IL-2R, but its role in myeloma remains unclear 44 .…”
Section: Discussionmentioning
confidence: 56%
“…Theories exist that involve amyloid deposits, the complement cascade, and cytokinemediated injury. 4 EDX studies confirm CIPN, identifying the nerve structures involved, the presence of axonal degeneration, and its severity. In the particular case of thalidomide, axonal damage compromises the amplitude of SNAPs, evidencing a decrease of 50% or more.…”
Section: Discussionmentioning
confidence: 85%
“…The obtained results highlighted the importance of the role of proinflammatory cytokines. Moreover, we demonstrated the previously unknown effect of complement components on the development of BiPN [ 13 ]. In another study, we depicted that the exposure of PC12-derived nerve cells to BTZ leads to alterations in the miRNA expression in genes responsible for cell cycle, DNA repair, nerve processes and cell division.…”
Section: Introductionmentioning
confidence: 71%